The Potension of Aditory Nerve Damage on Milling Industry Workers in Jember Regency - Jauhar Firdaus (Faculty of Medicine, University of Jember, 2020)
Jember Regency is one of the agro-industrial areas in Indonesia with a variety of activities that can produce noise including milling industry. Exposure to noise that is too strong or too long will damage the auditory nerve. The type of material being grounded determines the amount of noise produced so that the potential for hearing nerve damage also varies. This study aims to determine the level of noise produced by the milling industry and analyze the potential for hearing nerve damage in milling workers in Jember Regency. This type of research is observational analytic with cross-sectional approach. This research was conducted by measuring noise in several grinding locations in Jember that were randomly determined. Types of careful milling is grinding meat, coffee, rice, sticky rice and coconut. In addition to measuring the noise level, a short interview was also conducted with the mill workers regarding how long they worked at the mill every day. The measurement results are then analyzed descriptively and compared with standards set by the government and the Occupational Safety and Health Administration (OSHA). In this study it was found that the grinding of meat raw materials produced an average noise level of 88.5 db, coffee of 88.5 db, rice of 88.9 db, sticky rice of 87.3 db and coconut of 80.7 db. The duration of exposure to noise in milling meat, coffee, rice and sticky rice ranges from 9-12 hours a day. While the duration of noise exposure to coconut milling workers ranged from 6-9 hours. Therefore it can be concluded that milling meat, coffee, rice and sticky rice has the potential to cause hearing loss for workers. Keywords: agroindustry, hearing loss, noisy, milling